Identification of Inequalities in the Selection of Liver Surgery for Colorectal Liver Metastases in Sweden. (December 2018) - Norén, A.; Sandström, P.; Gunnarsdottir, K.; Ardnor, B.; Isaksson, B.; Lindell, G.; Rizell, M.
Background: Liver resection for colorectal liver metastases offers a 5-year survival rate of 25%–58%. This study aimed to analyze whether patients with colorectal liver metastases undergo resection to an equal extent and whether selection factors play a role in the selection process. Material and Methods: Data were retrieved from the Swedish Colorectal Cancer Registry (2007–2011) for colorectal cancer and colorectal liver metastases. The patients identified were linked to the Swedish Registry of Liver and Bile surgery and the National Patient Registry to identify whether liver surgery or ablative treatment was performed. Analyses for age, sex, type of primary tumor and treating hospital (university, county, or district), American Society of Anesthesiologists class, and radiology for detection of metastatic disease were performed. Results: Of 28, 355 patients with colorectal cancer, 21.6% (6127/28, 355) presented with liver metastases. Of the patients with liver metastases, 18.5% (1134/6127) underwent liver resection or ablation. The cumulative proportion of liver resection/ablation was 4% (1134/28, 355) of all colorectal cancer. If "not bowel resected" were excluded, the proportion slightly increased to 4.7% (1134/24, 262). Around 15% of the patients with metastases were registered as referrals for liver surgery. In a multivariable analysis patients treated at a university hospital for primary tumor were more frequently surgically treated for liver metastases (p < 0.0001). Patients with liver metastases from rectal cancer (p < 0.0001) and men more often underwent liver resection (p = 0.006). A difference was found between health-care regions for the frequency of liver surgery (p < 0.0001). Patients >70 years and those with American Society of Anesthesiologists class >2 underwent liver resection less frequently. Magnetic resonance imaging of the liver was more often used in diagnostic work-up in men. Conclusion: Patients with colorectal liver metastases are unequally treated in Sweden, as indicated by the low referral rate. The proximity to a hepatobiliary unit seems important to enhance the patient's chances of being offered liver surgery.